Oncologic patient navigation by nurses: a scoping review - José Mateus Pires; Andrea Bezerra Rodrigues; Mayara Maria Silva da Cruz Alencar; Régia Christina Moura Barbosa Castro (Universidade Federal do Ceará, 2024)
Objective: to map the navigation of oncologic patients by nurses in Brazil. Methods: this scoping review was conducted using the Medical Literature Analysis and Retrieval System, Scopus, Web of Science, Latin American and Caribbean Health Sciences Literature, and gray literature from the Brazilian Digital Library of Theses and Dissertations. Results: a total of 11 studies were selected that addressed the implementation and outcomes of oncology patient navigation programs, the development of supportive navigation technologies, and the prominent role of nursing in this context. Conclusion: oncology patient navigation by nurses in Brazil is essential for overcoming barriers to care, improving continuity, and enhancing the patient experience. Strengthening nurse training and incorporating supportive technologies are crucial for expanding this practice. Contributions to practice: this study reaffirms the central role of nursing in coordinating oncologic care, highlighting the effectiveness of navigation programs in improving the patient experience. It also emphasizes the importance of integrating supportive technologies and enhancing the training of nurse navigators to optimize oncologic care in Brazil.